Running medical education system and its development in China - Li, Ke; Chen, Hao (Frontiers in Education, 2025)
BackgroundThe Chinese government’s long-term healthcare strategy and the short-term pandemic of COVID-19 have highlighted the urgent need for clinically skilled and multidisciplinary-orientated healthcare professionals to address future healthcare challenges.ObjectiveThis systematic review analyzes the current state and future directions of medical education in China, drawing on various studies to provide insights into optimizing medical training and aligning it with national healthcare needs.MethodsA systematic review of existing literature on Chinese medical education reforms was conducted. The analysis focused on key aspects such as medical education systems, regional disparities, curriculum development, and management structures. Comparisons with international medical education models were also included to identify potential areas for improvement.DiscussionChina’s medical education system operates through multiple parallel mechanisms, with ongoing efforts to enhance regional coordination, diversify curricula, and improve collaboration between educational institutions and healthcare providers. Comparisons with foreign models suggest several key reforms: establishing a unified medical degree system with clear objectives, prioritizing general practitioners and primary care training, integrating medical humanities and public health education, and strengthening the governance of medical schools and affiliated hospitals.ConclusionThis systematic review provides a comprehensive overview of the evolving landscape of medical education in China, identifies challenges and opportunities, and proposes targeted reforms. These insights may serve as a reference for policymakers and educators working to enhance medical training and healthcare delivery in China.